2007
DOI: 10.4049/jimmunol.178.5.3134
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recognition of TLR-Dependent Microbial Ligands in Human Bronchial Epithelial Cells

Abstract: *Bronchial epithelial cells represent the first line of defense against invading airborne pathogens. They are important contributors to innate mucosal immunity and provide a variety of antimicrobial effectors. However, mucosal surfaces are prone to contact with pathogenic, as well as nonpathogenic microbes, and therefore, immune recognition principles have to be tightly controlled to avoid uncontrolled permanent activation. TLRs have been shown to recognize conserved microbial patterns and to mediate inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
154
0
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 167 publications
(181 citation statements)
references
References 56 publications
15
154
0
9
Order By: Relevance
“…However, only limited information is available for the situation in the upper airways. It has been reported that the sensitivity and the activation threshold of TLR in bronchial epithelial cells is indeed regulated [6,[14][15][16], supporting the concept that airway epithelial cells actively restrict pattern recognition principles.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…However, only limited information is available for the situation in the upper airways. It has been reported that the sensitivity and the activation threshold of TLR in bronchial epithelial cells is indeed regulated [6,[14][15][16], supporting the concept that airway epithelial cells actively restrict pattern recognition principles.…”
Section: Introductionmentioning
confidence: 81%
“…It has been shown convincingly that epithelial cells at surfaces that regularly or permanently encounter microbes express various TLR and are able to actively sense danger due to infectious agents [4][5][6][7][8]. This has two important implications: First, epithelial cells at non-sterile surfaces have to regulate their TLR sensitivity to avoid continuous threat of inflammation and, second, organ-specific mechanisms of regulating immunity have to exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations